PHARMACOTHERAPY AND LUNG FUNCTION DECLINE IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE : A SYSTEMATIC REVIEW - Radityo Prabowo, Galih (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Chronic obstructive pulmonary disease (COPD) is a long-term condition that affects millions of individuals all over the world and is a major contributor to the rise in hospital admission rates. According to projections made by the World Health Organization (WHO), COPD would become the third greatest cause of mortality worldwide by the year 2020. These patients are also very substantial consumers of the resources made available by the health and social care systems. Because there is now no treatment that can reverse the effects of COPD, patients are responsible for their own healthcare and the management of their condition. There is a correlation between the amount of cigarettes smoked and the degree to which COPD is present. The pathophysiology of COPD is intimately tied to the impact that cigarette smoke has on the lungs. Pharmacological trials that were carried out more than three decades ago with the use of short-acting bronchodilators or inhaled glucocorticoids did not succeed in demonstrating a statistically significant slower rate of FEV1 decline in comparison to the placebo group in their intention-to-treat populations. In light of these equivocal data, the belief that smoking cessation is the only treatment that can delay the course of COPD became widespread. Unfortunately, this pessimism has had a negative impact on how the general public views COPD and has decreased interest in alternative therapeutic techniques. Tiotropium had a greater FEV1 than the placebo, and it also reduced the annual reduction in FEV1 after bronchodilator usage in individuals with COPD who were in the GOLD stage 1 or 2 range. FEV1 drop might be stopped by FF or VI. The patients expressed satisfaction with the treatment, which resulted in fewer exacerbations. It seems like fluticasone furoate or vilanterol could slow down the drop in FEV1 levels.